2012
DOI: 10.1371/journal.pone.0052521
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of Decapping Protein 2 Mediates Chronic Nicotine Exposure-Induced Locomotor Hyperactivity in Drosophila

Abstract: Long-term tobacco use causes nicotine dependence via the regulation of a wide range of genes and is accompanied by various health problems. Studies in mammalian systems have revealed some key factors involved in the effects of nicotine, including nicotinic acetylcholine receptors (nAChRs), dopamine and other neurotransmitters. Nevertheless, the signaling pathways that link nicotine-induced molecular and behavioral modifications remain elusive. Utilizing a chronic nicotine administration paradigm, we found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…To test the dosage dependent effects of nicotine on locomotor activity, we tested with four concentrations in addition to 0.6 mM of nicotine. In our previous study, we reported that 3.0 mM nicotine in food induced chronic locomotor hyperactivity (Ren et al, 2012). In this study, we found that acute treatment of nicotine at 3.0 mM induced locomotor hyperactivity in female flies, not however, in male flies.…”
Section: Nicotine Administration Induces Acute Locomotor Hyperactivitsupporting
confidence: 46%
See 1 more Smart Citation
“…To test the dosage dependent effects of nicotine on locomotor activity, we tested with four concentrations in addition to 0.6 mM of nicotine. In our previous study, we reported that 3.0 mM nicotine in food induced chronic locomotor hyperactivity (Ren et al, 2012). In this study, we found that acute treatment of nicotine at 3.0 mM induced locomotor hyperactivity in female flies, not however, in male flies.…”
Section: Nicotine Administration Induces Acute Locomotor Hyperactivitsupporting
confidence: 46%
“…In the startle-induced negative geotaxis assay using vertical columns, flies showed reduced climbing activity in response to nicotine treatment, and the acute and long-lasting effects were found to be mediated by dopaminergic system and cAMP/CREB pathway, respectively (Bainton et al, 2000, Hou et al, 2004. Using a video recording system where flies are tested in horizontal tubes (Zimmerman et al, 2008), our previous study revealed that chronic nicotine treatment induces locomotor hyperactivity in flies, and a protein in the decapping complex, decapping protein 2, was found to be a key factor in mediating nicotine-induced locomotor hyperactivity (Ren et al, 2012). Early onset of hyperactivity upon nicotine exposure has been observed in flies, though the mechanistic details behind this observation have so far not been studied (Bainton et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The mRNA level for Dcp2 is upregulated 1.3-fold in the pcm 5 mutant, while its pre-mRNA is 1.1-fold downregulated. Although these changes are statistically significant, they are very small (< 30%) and unlikely to be biologically significant, because a 4-fold increase in Dcp2 protein level (by expression of a transgene) generates no mutant phenotypes when flies are grown under normal conditions 25 . For CG7966 and CG31157 , the mRNA levels of which do not change in the pcm 5 mutant, the pre-mRNA levels also do not change.…”
Section: Resultsmentioning
confidence: 93%
“…More recently, Zhang et al showed that dopamine also mediates the chronic nicotine exposure-induced locomotor hyperactivity in adult flies described by Ren et al [42,69]. In mammals and Drosophila , alpha7 receptors have been associated to biogenic amine release [41,63].…”
Section: Discussionmentioning
confidence: 99%